Pembentukan Karakter Religius Santri Putra melalui Program Membaca Al-Qur’an dan Sholat Dhuha di PPTQ Al-Mustaqimiyyah - Muhamad Fathi (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Religious character is one aspect of character values related to an individual's relationship with God. Religious character is considered a key point that needs to be instilled and developed from an early age in children. This serves as the foundation of religious teachings in the lives of individuals and society as a whole. The aim of this research is to understand the formation of religious character among Islamic boarding school students through the programs of reading the Quran and performing the Dhuha prayer at PPTQ Al-Mustaqimiyyah. The research method used is qualitative, employing data collection techniques such as observation, interviews, and documentation. Data sources were obtained through interviews with administrators, teachers, and students. The results indicate that the Quran reading and Dhuha prayer program has a positive impact on shaping the religious character of the students. This is reflected in the improvement of Quran reading skills, awareness in worship, discipline, responsibility, honesty, and the cultivation of good morals, attitudes, and behavior. With these activities, it is expected that students will be motivated and enthusiastic to enhance their memorization of the Quran, not only by reading and memorizing but also by understanding the meaning of the sacred verses and applying them in community life. The improvement in worship is expected to help them distinguish between noble moral values and reprehensible behavior, forming good habits that are difficult to replace in the future.